SUN-132 KLF5 Is a Poor Prognostic Marker and Therapeutic Target for Middle Eastern Papillary Thyroid Carcinoma - Al-Kuraya, Khawla S (J Endocr Soc, 2020)
Thyroid cancer is the second most common malignancy among females in Saudi Arabia, with Papillary thyroid carcinoma (PTC) accounting for 80-90%. The Kruppel-like factor 5 (Klf5) is a transcription factor that play a critical role in cell transformation, proliferation and oncogenesis. Immunohistochemical analysis of KLF5 was performed in 1219 PTC cases. KLF5 over-expression was noted in 65.1% (793/1219) of PTCs, and was significantly associated with tall-cell variant (p <0.0001), extrathyroidal extension (p = 0.0003), lymph node metastasis (p < 0.0001) and stage IV tumors (p < 0.0001). Significant association was also noted with HIF-1α over-expression (p = 0.0492). Interestingly, KLF5 over-expressing tumors showed poor disease-free survival (p = 0.0066). Functional studies in PTC cell lines showed that KLF5 co-immunoprecipitated with HIF-1α. Knockdown of KLF5 decreased the expression of HIF-1α while KLF5 was not affected by HIF-1α inhibition, suggesting that KLF5 is a functional upstream of HIF-1α. Down-regulation of KLF5 using specific inhibitor, ML264 or siRNA inhibited cell invasion and migration. In addition, treatment of PTC cell lines with ML264 resulted in inhibition of proliferation and induction of apoptosis in a dose-dependent manner. Furthermore, silencing of KLF5 significantly decreased the self-renewal ability of spheroids generated from PTC cells. Our findings confer that KLF5 may be a potential therapeutic target for the treatment of papillary thyroid cancer.